Highly water-absorbent resin and method for producing same

By using hydrophobic particles with varying sizes in an aqueous dispersion to stabilize bubbles during polymerization, the method creates a highly porous superabsorbent resin with improved water absorption rates and surface tension, addressing the challenges of pulpless diapers.

JP7618342B2Active Publication Date: 2025-01-21LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023514144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-16
Filing Date
2021-12-17
Publication Date
2025-01-21
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Existing superabsorbent resins used in pulpless diapers face challenges in achieving high water absorption rates and maintaining physical properties due to unstable bubble formation during polymerization, which is exacerbated by the use of bubble stabilizers that can deteriorate resin quality.

Method used

A method involving the use of two types of hydrophobic particles with different average sizes in an aqueous dispersion during polymerization to stabilize air bubbles and form a highly developed porous structure with uniform micropores, minimizing the need for surfactant-type bubble stabilizers, resulting in improved water absorption rates and surface tension.

Benefits of technology

The developed porous structure enhances water absorption rates and maintains excellent physical properties, making the resin suitable for pulpless and ultra-thin diapers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618342000002
    Figure 0007618342000002
  • Figure 0007618342000003
    Figure 0007618342000003
  • Figure 0007618342000001
    Figure 0007618342000001
Patent Text Reader

Abstract

The present invention relates to a superabsorbent polymer and a manufacturing method thereof. More specifically, the present invention relates to a superabsorbent polymer that has an average of seven or more micropores per particle, each having an average diameter of 100 μm or less and a maximum diameter of 300 μm or less, and exhibits improved water absorption rate and high surface tension, and a manufacturing method for the superabsorbent polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Applications Nos. 10-2020-0178428 and 10-2021-0180575 dated December 18, 2020, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a superabsorbent polymer and a method for producing the same. More specifically, the present invention relates to a superabsorbent polymer that contains a large number of micropores and exhibits an improved water absorption rate and high surface tension, and a method for producing the same. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric material that can absorb 500 to 1,000 times its own weight in water, and is given different names by different developers, such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). Such super absorbent polymers were first put to practical use as sanitary products, and are now widely used as materials for gardening soil repair agents, civil engineering and architectural waterproofing materials, seedling sheets, freshness preserving agents in the food distribution field, and for dripping.

[0004] Such superabsorbent polymers are widely used in the field of sanitary products, such as diapers and sanitary belts. In the sanitary products, the superabsorbent polymers are generally contained in a state of being spread in the pulp. However, in recent years, there have been ongoing efforts to provide sanitary products, such as diapers, with thinner thicknesses, and as part of these efforts, the pulp content has been reduced or even no pulp is used at all, so-called pulpless diapers, have been actively developed.

[0005] The superabsorbent resins used in sanitary materials such as pulpless diapers, which have a reduced pulp content or no pulp used, must not only function as an absorbent that absorbs liquids such as urine, but also as pulp, and therefore must exhibit not only high water absorption performance but also a fast water absorption speed.

[0006] In order to prepare a superabsorbent resin having an improved water absorption rate, a method of improving the specific surface area by introducing a pore structure into the superabsorbent resin is mainly used. Specifically, in order to improve the specific surface area of ​​the superabsorbent resin, a foaming agent can be used to generate bubbles in the polymerization step, or gas such as carbon dioxide gas, air, or nitrogen gas can be injected. However, since bubbles are unstable in the neutralization solution, if a bubble stabilizer capable of capturing the bubbles is not used, the bubbles will escape outside the neutralization solution, making it impossible to prepare a superabsorbent resin having a pore structure. In addition, if the bubble stabilizer is used in an excessive amount, there is a problem that various physical properties of the superabsorbent resin are deteriorated.

[0007] For this reason, there is a continuing demand for the development of superabsorbent polymers that exhibit a high water absorption rate while maintaining the basic water absorption performance of the superabsorbent polymers. Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, the present invention relates to a superabsorbent resin having a developed porous structure including a large number of predetermined micropores, thereby exhibiting an improved water absorption rate and excellent physical properties such as high surface tension, and a method for producing the same. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides A base resin in powder form containing a crosslinked polymer of an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and an internal crosslinking agent; and A highly water-absorbent resin comprising a surface cross-linked layer formed on the base resin and in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent, The superabsorbent resin has an average of 7 or more pores per particle, the pores have an average diameter of 100 μm or less and a maximum diameter of 300 μm or less, and particles having pores having a diameter between the average diameter and the maximum diameter account for 10 to 50% by number of all superabsorbent resin particles, The superabsorbent resin has a surface tension of 65 mN / m or more and a water absorption rate (vortex time) of 40 seconds or less at 24.0° C.

[0010] The present invention also provides a method for producing a semiconductor device comprising the steps of: A step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, a polymerization initiator, an internal crosslinking agent, and an aqueous dispersion of hydrophobic particles (step 1); a step of cross-linking and polymerizing the monomer composition in the presence of a foaming agent or bubble generator to produce a hydrogel polymer (step 2); drying and grinding the hydrogel polymer to form a base resin in powder form (Step 3); and Step 4 includes a step of further crosslinking the surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer, The hydrophobic particle aqueous dispersion is a colloidal solution in which first hydrophobic particles and second hydrophobic particles are dispersed, and the ratio of the average particle size of the second hydrophobic particles to the average particle size of the first hydrophobic particles is 5 to 100. Effect of the Invention

[0011] The superabsorbent polymer of the present invention has a highly developed porous structure that includes many micropores having an average diameter of 100 μm or less and a maximum diameter of 300 μm or less, and in particular has many pores having very uniform diameters, resulting in a significantly increased specific surface area of ​​the superabsorbent polymer, thereby enabling the polymer to exhibit an improved water absorption rate.

[0012] Such a superabsorbent polymer can be prepared by adding two types of hydrophobic particles having different particle sizes in the form of an aqueous dispersion during the polymerization step. The use of such hydrophobic particles results in the formation of a superabsorbent polymer having a highly developed porous structure, while minimizing or eliminating the need for surfactants that are typically used as bubble stabilizers, thereby minimizing the resulting decrease in physical properties such as the surface tension of the superabsorbent polymer.

[0013] Therefore, according to the present invention, it is possible to provide a superabsorbent resin which exhibits an excellent water absorption rate and other excellent physical properties and is preferably used in pulpless diapers or ultra-thin diapers. [Brief description of the drawings]

[0014] [Figure 1] 1 is a SEM image of the superabsorbent resin produced in Example 3. [Diagram 2] 1 is a SEM image of the superabsorbent resin prepared in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.

[0016] The present invention can be modified in various ways and can have various forms, and the following detailed description will be given by way of examples of specific embodiments, but it should be understood that the present invention is not limited to the specific disclosed embodiments, but includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.

[0017] Furthermore, the terminology used in this specification is for the purpose of referring to particular embodiments only and is not intended to limit the present invention. Additionally, as used herein, the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise.

[0018] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the above polymers, a polymer in a state after polymerization and before drying and having a water content (water content) of about 40% by weight or more can be called a hydrogel polymer, and particles obtained by crushing and drying such a hydrogel polymer can be called a crosslinked polymer.

[0019] In addition, the term "superabsorbent resin particles" refers to a particulate material including a crosslinked polymer obtained by polymerizing an acrylic acid monomer having acidic groups and at least a portion of the acidic groups being neutralized and crosslinking the polymer with an internal crosslinking agent.

[0020] In addition, the term "crosslinked polymer" refers to a polymer having a three-dimensional network structure in which the main chain formed by polymerization of the acrylic acid monomer is crosslinked by the internal crosslinking agent.

[0021] In addition, depending on the context, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, or a base resin in the form of a powder consisting of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Thus, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.

[0022] The term "average diameter" of the pores means the average value of the longest diameter of each of the plurality of pores contained in the highly water-absorbent polymer.

[0023] The term "maximum diameter" of a pore means the maximum value among the longest diameters of each of a plurality of pores contained in the highly water-absorbent polymer.

[0024] In order to produce a superabsorbent resin having a high water absorption rate, the specific surface area in the superabsorbent resin particles must be increased. Thus, in order to realize a superabsorbent resin with a high specific surface area, a method of forming a large number of pores in the superabsorbent resin by inducing a foaming process during the production process or a method of mechanically deforming the superabsorbent resin has been used. However, in the case of a method of producing a superabsorbent resin by a foaming process, a surfactant-type foam stabilizer is used because the bubbles generated during the process are trapped inside the polymer and do not escape to the outside of the crosslinked polymer. When such a foam stabilizer is used, the pores are large and have a wide range of pore sizes, and the aspect ratio of the superabsorbent resin particles is low, so that they are easily broken depending on the process environment, or the physical properties under pressure are reduced due to non-uniform surface crosslinking efficiency. In addition, in the case of a method of producing a superabsorbent resin by mechanical deformation, excessive equipment load increases during the process, leading to a decrease in productivity.

[0025] Therefore, the present inventors confirmed that when two kinds of hydrophobic particles with different average particle diameters are used in the form of an aqueous dispersion instead of a commonly used bubble stabilizer, a superabsorbent resin having a developed pore structure in which a plurality of pores having an average diameter of 100 μm or less and a maximum diameter of 300 μm or less are formed on average 7 or more per superabsorbent resin particle. In addition, such a superabsorbent resin may have pores having a diameter of the average diameter or more and the maximum diameter or less, i.e., particles having one or more pores with a relatively large diameter, which may account for 10 to 50% by number of the total superabsorbent resin particles. This indicates that the number of particles having pores with a relatively large diameter is not large, and that micropores having a diameter close to or slightly smaller than the average diameter are distributed very uniformly on the superabsorbent resin particles. Therefore, the superabsorbent resin may have a developed porous structure in which micropores having a diameter that is not relatively large are distributed very uniformly in large numbers.

[0026] It was confirmed that the superabsorbent resin not only exhibits an ultra-high water absorption rate but also has high surface tension due to such a highly developed porous structure.Specifically, when two types of hydrophobic particles with different particle sizes are added in the form of an aqueous dispersion in the monomer polymerization step, it is possible to produce a superabsorbent resin having a highly developed porous structure in which small and uniform pores are uniformly distributed throughout the entire crosslinked polymer by effectively capturing and stabilizing bubbles generated by a foaming agent or bubble generator, even if the bubble stabilizer is not added at all, or by minimizing the addition of a separate surfactant type bubble stabilizer.

[0027] More specifically, in the method for producing a superabsorbent resin according to one embodiment, two types of hydrophobic particles are not used in powder form, but are added to the monomer composition in the form of a "hydrophobic particle aqueous dispersion," i.e., in the form of a colloidal solution in which the hydrophobic particles are stably dispersed without precipitating or agglomerating. This is because, when the hydrophobic particles are added in powder form to the monomer composition to carry out the polymerization process, the hydrophobic particles do not disperse in the monomer composition in the form of an aqueous solution, and the bubbles generated due to precipitation cannot be effectively stabilized.

[0028] In addition, each hydrophobic particle is stably dispersed in the aqueous dispersion liquid by the dispersion stabilizer without inter-particle aggregation. Specifically, the dispersion stabilizer can form an electric double layer on the surface of the hydrophobic particle to induce an electrostatic repulsive force between particles to stabilize the hydrophobic particles, or can be adsorbed on the surface of the hydrophobic particle to induce a steric repulsive force between particles to prevent the particles from aggregating with each other. Therefore, if the hydrophobic particle aqueous dispersion liquid does not contain such a dispersion stabilizer, the hydrophobic particles will aggregate with each other or sink due to gravity, and the dispersion stabilization of the hydrophobic particles will not be achieved. Therefore, if the hydrophobic particle aqueous dispersion liquid not containing a dispersion stabilizer is used together with a blowing agent in the polymerization step, it is difficult to effectively capture air bubbles and form pores in the superabsorbent resin, so that the water absorption rate of the superabsorbent resin is difficult to improve. However, the types of such dispersion stabilizers will be described in more detail in the manufacturing method described below.

[0029] In addition, the first hydrophobic particles have an average particle size of less than 1 μm, and the second hydrophobic particles have an average particle size of 1 μm or more. This is because when large and small particles are present together, the surface energy of bubbles in the monomer composition can be reduced, and small bubbles can be stably maintained even in a small amount. As a result, the superabsorbent resin according to one embodiment exhibits improved water absorption speed and high surface tension, and is very suitable for use in various sanitary materials.

[0030] Hereinafter, the superabsorbent polymer and the method for producing the superabsorbent polymer will be described in detail step by step according to specific embodiments of the present invention.

[0031] Super absorbent resin According to one embodiment, the superabsorbent resin includes a powder-form base resin including a crosslinked polymer of an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and an internal crosslinking agent; and a surface crosslinked layer formed on the base resin, the crosslinked polymer being additionally crosslinked via a surface crosslinking agent.

[0032] In particular, the superabsorbent polymer is a porous superabsorbent polymer having a plurality of pores, each of which has an average diameter of 100 μm or less and a maximum diameter of 300 μm or less. In this case, if the average diameter of the plurality of pores contained in the superabsorbent polymer exceeds 100 μm or the maximum diameter exceeds 300 μm, the specific surface area of ​​the superabsorbent polymer is not sufficiently secured, and it is difficult to expect an improvement in the water absorption rate. In addition, such a superabsorbent polymer may have a surface of particles that are easily worn or broken during processing, resulting in a decrease in physical properties and an increase in fine powder. Therefore, the superabsorbent polymer according to the embodiment has a pore structure in which fine pores are uniformly distributed, and thus has a significantly improved water absorption rate and high water absorption capacity, compared to a porous superabsorbent polymer having a plurality of pores with an average diameter of 100 μm or less and a maximum diameter of more than 300 μm.

[0033] As an example, the plurality of pores contained within the highly water-absorbent resin may have an average diameter of 1 μm to 100 μm and a maximum diameter of 250 μm to 300 μm.

[0034] Furthermore, the superabsorbent resin may contain an average of 7 or more, or 7 to 30, pores each having the aforementioned average and maximum diameters per particle of the superabsorbent resin.

[0035] In addition, among the plurality of pores, pores having a diameter between the average diameter and the maximum diameter, i.e., pores having a relatively large diameter, may be formed only on particles corresponding to 10-50% by number, or 20-40% by number, of the total superabsorbent resin particles. This may mean that a large number of micropores having a diameter close to or slightly smaller than the average diameter are formed with a very uniform and narrow diameter distribution on more than half of the superabsorbent resin particles. Therefore, the superabsorbent resin may have a developed pore structure in which a large number of micropores having a very uniform diameter are formed in most of the particles.

[0036] Due to such a highly developed porous structure, the superabsorbent resin can exhibit a significantly improved water absorption rate. In contrast, a superabsorbent resin produced by foaming using a conventional foaming agent or a bubble generator without using a hydrophobic particle aqueous dispersion does not have a sufficiently developed porous structure because of difficulty in stabilizing the bubbles, or requires the use of a considerable amount of a bubble stabilizer, which can reduce the surface tension and other physical properties of the superabsorbent resin.

[0037] Meanwhile, the average diameter and maximum diameter of the pores in the superabsorbent polymer, the average number of pores per particle, and the ratio of particles having relatively large pores can be confirmed by observing the surface and / or internal image of the superabsorbent polymer particles to be measured using an electron microscope. More specifically, the longest diameter of each pore contained in the superabsorbent polymer particle is measured, and the average value of the longest diameters of the measured pores is taken as the average diameter, and the maximum value is taken as the maximum diameter. In addition, the number of pores whose longest diameter can be measured using an electron microscope can be calculated, and the average number of pores per particle can be measured and calculated. When the longest diameter of the pores is equal to or greater than the average diameter, the number of pores and the number of particles in which the pores are formed can be measured, and the ratio of particles in which pores having a diameter greater than the average diameter and less than the maximum diameter can be calculated. At this time, it is preferable to select 300 or more pores from one superabsorbent polymer sample (e.g., a superabsorbent polymer sample manufactured through a single process), measure the diameters thereof, and then determine the average diameter and maximum diameter.

[0038] The acrylic acid monomer is a compound represented by the following formula 1:

[0039] [Chemical formula 1] R 1 -COOM 1

[0040] In the above chemical formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0041] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0042] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree may be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate, making it difficult to smoothly carry out polymerization, and conversely, if the neutralization degree is too low, the water absorption of the polymer may be greatly reduced and the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.

[0043] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition including the raw material of the superabsorbent polymer and the solvent, and may be an appropriate concentration in consideration of the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent polymer may be low, causing problems in economic efficiency, and conversely, if the concentration is too high, problems may occur in the process, such as a part of the monomer being precipitated or the efficiency of pulverization of the polymerized hydrogel polymer being low, and the physical properties of the superabsorbent polymer may be deteriorated.

[0044] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of the superabsorbent resin particles described below, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed regardless of the surface or the inside, but when the surface crosslinking process of the superabsorbent resin particles described below is performed, the particle surface of the finally produced superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0045] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking bonds during polymerization of the acrylic unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.

[0046] Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, etc. Acrylate-based compounds; epoxy-based compounds such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether; triarylamines; propylene glycol; glycerin; or polyfunctional crosslinkers such as ethylene carbonate, which may be used alone or in combination of two or more, but are not limited thereto.

[0047] The crosslinking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of such an internal crosslinking agent may be carried out by thermal polymerization, photopolymerization or hybrid polymerization in the presence of a polymerization initiator and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, etc., the details of which will be described later.

[0048] In addition, the superabsorbent resin further includes a surface cross-linked layer formed by additionally cross-linking the cross-linked polymer contained in the base resin via a surface cross-linking agent on at least a part of the surface of the base resin, in order to increase the surface cross-linking density of the superabsorbent resin. When the superabsorbent resin further includes a surface cross-linked layer as described above, the superabsorbent resin has a structure in which the cross-linking density is higher on the outside than on the inside.

[0049] The surface cross-linking agent may be any surface cross-linking agent used in the manufacture of existing superabsorbent resins without any particular limitation. For example, the surface cross-linking agent may include at least one selected from the group consisting of polyhydric alcohol compounds, polyfunctional epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, and alkylene carbonate compounds.

[0050] Specifically, examples of the polyhydric alcohol compound include mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.

[0051] The polyfunctional epoxy compound may be ethylene glycol diglycidyl ether or glycidol.

[0052] The polyamine compound may be ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, polyamidepolyamine, or the like.

[0053] As the haloepoxy compound, epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, or the like can be used.

[0054] As the oxazoline-based compound, mono-, di- or polyoxazolidinones can be used.

[0055] As the alkylene carbonate compound, ethylene carbonate, propylene carbonate, glycerol carbonate, or the like can be used.

[0056] More specifically, the surface cross-linking agent may be one of the above-mentioned surface cross-linking agents, or may be used in combination with one another. For example, an alkylene carbonate compound such as ethylene carbonate may be used as the surface cross-linking agent.

[0057] In addition, the highly absorbent resin may include first hydrophobic particles and second hydrophobic particles, in which the first hydrophobic particles have an average particle size of less than 1 μm, and the second hydrophobic particles have an average particle size of 1 μm or more.

[0058] Here, hydrophobic particles refer to water-insoluble particles that have a contact angle with water of 50° or more or that do not dissolve in water. Particles with a contact angle with water of less than 50° and water-soluble particles can dissolve in a monomer composition in the form of an aqueous solution and are therefore unlikely to capture bubbles generated during the polymerization process, whereas hydrophobic particles are positioned at the interface between bubbles of carbon dioxide or other substances that have hydrophobic properties within the neutralization liquid and the neutralization liquid, thereby effectively capturing and stabilizing the bubbles.

[0059] Therefore, the first hydrophobic particles and the second hydrophobic particles each have a contact angle with water of 50° or more. More specifically, the first hydrophobic particles and the second hydrophobic particles each may have a contact angle with water of 70° or more, 100° or more, 120° or more, or 150° or more, and may be 175° or less.

[0060] At this time, the contact angles of the first and second hydrophobic particles can be measured by the following method. First, a coating solution is prepared by dispersing each hydrophobic particle in a methylene chloride solvent at a concentration of 5% by weight. Then, the coating solution is spin-coated on a wafer with no surface roughness, and the remaining solvent is removed by drying at room temperature. Then, water is dropped dropwise onto the coating layer, and the contact angle is measured, which is defined as the contact angle of each hydrophobic particle.

[0061] In addition, the first hydrophobic particles have an average particle size of less than 1 μm, specifically 10 nm or more and less than 1 μm. More specifically, the average particle size of the first hydrophobic particles may be 10 nm or more, 50 nm or more, or 100 nm or more, but 800 nm or less, 600 nm or less, 400 nm or less, or 300 nm or less.

[0062] The second hydrophobic particles have an average particle size of 1 μm or more, specifically, 1 μm to 100 μm. More specifically, the average particle size of the second hydrophobic particles may be 2 μm or more, or 3 μm or more, and 50 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, or 7 μm or less.

[0063] Here, the average particle size of the hydrophobic particles means D50, and the "particle size Dn" means the particle size at n% of the cumulative particle number distribution according to particle size. That is, D50 is the particle size at 50% of the cumulative particle number distribution according to particle size, D90 is the particle size at 90% of the cumulative particle number distribution according to particle size, and D10 is the particle size at 10% of the cumulative particle number distribution according to particle size. The Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and when the particles pass through a laser beam, the diffraction pattern difference according to the particle size is measured to calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle diameter at 10%, 50%, and 90% of the cumulative particle number distribution according to particle size in the measuring device.

[0064] In addition, the ratio of the average particle size of the second hydrophobic particles to the average particle size of the first hydrophobic particles may be 5 to 100, more specifically, 10 to 50. If the second hydrophobic particles have an excessively small average particle size compared to the first hydrophobic particles, or if the second hydrophobic particles have an excessively large average particle size compared to the first hydrophobic particles, it may be difficult to capture small air bubbles, and the size of the air bubbles may become large.

[0065] Also, the first hydrophobic particles and the second hydrophobic particles may be included in a weight ratio of 1:5 to 1:50. If the second hydrophobic particles are included in an excessively small amount compared to the first hydrophobic particles, it may be difficult to capture and maintain gas in the monomer composition, and if the second hydrophobic particles are included in an excessively large amount compared to the first hydrophobic particles, the size of the pores may be large. For example, the second hydrophobic particles may be used in an amount of 6 times or more, 8 times or more, or 10 times or more, or may be included in an amount of 40 times or less, 30 times or less, or 20 times or less, compared to the weight of the first hydrophobic particles.

[0066] Moreover, the first hydrophobic particles and the second hydrophobic particles can be independently selected from the group consisting of hydrophobic silica, metal salts of fatty acids having 7 to 24 carbon atoms, and hydrophobic organic particles.

[0067] Specifically, the first hydrophobic particles and the second hydrophobic particles are all hydrophobic silica; or One of the first hydrophobic particles and the second hydrophobic particles is hydrophobic silica, and the other is a metal salt of a fatty acid having 7 to 24 carbon atoms; The first hydrophobic particles and the second hydrophobic particles may all be metal salts of fatty acids having 7 to 24 carbon atoms.

[0068] Here, hydrophobic silica is a general term for silica that has a low content of silanol (-SiOH) on the surface and has a contact angle with water of 50° or more, and any hydrophobic silica known in the art can be used without limitation.

[0069] In addition, the metal salt of a fatty acid having 7 to 24 carbon atoms refers to a compound in which a metal cation is bonded instead of a hydrogen ion of a carboxyl group at the end of an unsaturated or saturated fatty acid having a linear structure while having 7 to 24 carbon atoms in the molecule, and in this case, the metal salt may be a monovalent metal salt or a polyvalent metal salt having a valence of 2 or more. In this case, when the hydrophobic particles are metal salts of fatty acids having less than 7 carbon atoms, it is not possible to capture air bubbles that are ionized in an aqueous solution and generated in the form of particles, and when the hydrophobic particles are metal salts of fatty acids having more than 24 carbon atoms, the fatty acid chains become long and dispersion may be difficult.

[0070] Specifically, when the metal salt of the fatty acid is a monovalent metal salt, it has a structure in which one fatty acid carboxylate anion is bound to an alkali ion, which is a monovalent metal cation, and when the metal salt of the fatty acid is a polyvalent metal salt, it has a structure in which fatty acid carboxylate anions are bound to a metal cation in the number equal to the valence of the metal cation.

[0071] In one embodiment, the hydrophobic particles may be a metal salt of a saturated fatty acid having 12 to 20 carbon atoms. For example, the hydrophobic particles may be one or more metal salts of saturated fatty acids selected from the group consisting of a metal salt of lauric acid containing 12 carbon atoms in the molecule, a metal salt of tridecylic acid containing 13 carbon atoms in the molecule, a metal salt of myristic acid containing 14 carbon atoms in the molecule, a metal salt of pentadecanoic acid containing 15 carbon atoms in the molecule, a metal salt of palmitic acid containing 16 carbon atoms in the molecule, a metal salt of margaric acid containing 17 carbon atoms in the molecule, a metal salt of stearic acid containing 18 carbon atoms in the molecule, a metal salt of nonadecylic acid containing 19 carbon atoms in the molecule, and a metal salt of arachidic acid containing 20 carbon atoms in the molecule.

[0072] Preferably, the metal salt of a fatty acid may be a metal stearate, such as one or more metal salts of stearic acid selected from the group consisting of calcium stearate, magnesium stearate, sodium stearate, zinc stearate, and potassium stearate.

[0073] The hydrophobic organic particles may also be one or more hydrophobic polymer particles selected from the group consisting of ethylene polymers, propylene polymers, styrene polymers, butadiene polymers, styrene-butadiene copolymers, alkyl acrylate polymers, alkyl methacrylate polymers, alkyl acrylate-acrylonitrile copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-alkyl acrylate-styrene copolymers, alkyl methacrylate-butadiene-styrene copolymers, and alkyl acrylate-alkyl methacrylate copolymers.

[0074] Meanwhile, the superabsorbent resin may contain particles having a particle size of about 150 to about 850 μm in an amount of 90% by weight or more, or 90 to 100% by weight, based on the total weight, and the particle size of such superabsorbent resin particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP220.3 method. The average pore diameter, maximum diameter, average number of pores per particle, and ratio of particles having pores of a predetermined diameter may be measured and calculated for the superabsorbent resin particles having a particle size of 150 to about 850 μm.

[0075] The superabsorbent resin may have a water absorption rate (vortex time) of 40 seconds or less, 39 seconds or less, or 38 seconds or less at 24.0° C. The smaller the water absorption rate, the better, and the lower limit of the water absorption rate is theoretically 0 seconds, but may be, for example, 5 seconds or more, 10 seconds or more, or 20 seconds or more. At this time, the method for measuring the water absorption rate of the superabsorbent resin will be described in more detail in the Examples below.

[0076] In addition, the superabsorbent polymer may have a surface tension of 65 mN / m or more, 66 mN / m or more, or 68 mN / m or more, and 72 mN / m or less, or 71 mN / m or less. In this case, a method for measuring the surface tension of the superabsorbent polymer will be described in more detail in the Examples below.

[0077] In addition, the superabsorbent polymer may have a centrifuge retention capacity (CRC) of greater than 27 g / g as measured by EDANA method WSP241.3, and an absorbent capacity under pressure (AUP) at 0.7 psi as measured by EDANA method WSP242.3 of greater than 20 g / g. More specifically, the superabsorbent polymer may have a centrifuge retention capacity (CRC) of 27.5 g / g or more, or 28 g / g or more, but 34 g / g or less, or 33 g / g or less, as measured by EDANA method WSP241.3. The superabsorbent polymer may also have an absorbent capacity under pressure (AUP) at 0.7 psi as measured by EDANA method WSP242.3 of 21 g / g or more, 22 g / g or more, or 23 g / g or more, but 28 g / g or less, or 27 g / g or less.

[0078] Manufacturing method of superabsorbent resin Meanwhile, the superabsorbent resin may be prepared by the steps of: preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, a polymerization initiator, an internal crosslinking agent, and an aqueous dispersion of hydrophobic particles (Step 1); crosslinking the monomer composition in the presence of a foaming agent or a bubble generator to prepare a hydrogel polymer (Step 2); drying and pulverizing the hydrogel polymer to form a powdered base resin (Step 3); and additionally crosslinking the surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer (Step 4).

[0079] Here, the hydrophobic particle aqueous dispersion is a colloidal solution in which first hydrophobic particles and second hydrophobic particles are dispersed, and the ratio of the average particle size of the second hydrophobic particles to the average particle size of the first hydrophobic particles is 5 to 100.

[0080] In this case, the hydrophobic particle aqueous dispersion may be in the form of an aqueous dispersion containing both the first hydrophobic particles and the second hydrophobic particles, or may be in the form of a mixture of a first hydrophobic particle aqueous dispersion in which the first hydrophobic particles are dispersed and a second hydrophobic particle aqueous dispersion in which the second hydrophobic particles are dispersed.

[0081] In addition, the first hydrophobic particles have an average particle size of less than 1 μm, and the second hydrophobic particles have an average particle size of 1 μm or more. For other explanations regarding the first hydrophobic particles and the second hydrophobic particles, please refer to the above.

[0082] Hereinafter, each step of the method for producing a highly water-absorbent resin according to one embodiment will be described in detail.

[0083] (Stage 1) The step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which is neutralized, a polymerization initiator, an internal crosslinking agent, and a hydrophobic particle aqueous dispersion is described above. For the description of the acrylic acid monomer and the internal crosslinking agent, please refer to the above.

[0084] The first hydrophobic particles and the second hydrophobic particles may be contained in the aqueous dispersion in an amount of 0.01 to 60% by weight based on the total weight of the aqueous dispersion. If the content of the hydrophobic particles in the aqueous dispersion is too low, the attraction force between the particles is reduced, improving the dispersion stability, but there is a problem that a large amount must be added when preparing the superabsorbent resin, and if the content of the hydrophobic particles in the aqueous dispersion is too high, there is a problem that the dispersion stability is reduced due to aggregation between the particles. However, the content of the hydrophobic particles in the aqueous dispersion is appropriate to be as high as possible within a range in which the dispersion stability can be ensured. This is because the higher the content of the hydrophobic particles in the aqueous dispersion, the better the air bubble collecting ability, and the more developed porous structure and improved water absorption speed of the superabsorbent resin can be obtained.

[0085] Meanwhile, the first hydrophobic particles and the second hydrophobic particles may be uniformly dispersed in the aqueous dispersion by a dispersion stabilizer such as a surfactant or a polymer surrounding the particle surface. The surfactant mainly forms an electric double layer on the surface of the hydrophobic particles to induce an electrostatic repulsive force between particles, thereby stabilizing the hydrophobic particles and improving the dispersion stability of the hydrophobic particles. And, the polymer is adsorbed on the surface of the hydrophobic particles to induce a steric repulsive force between particles, thereby preventing the particles from agglomerating with each other, thereby improving the dispersion stability of the hydrophobic particles.

[0086] For example, the surfactant may be one or more surfactants selected from the group consisting of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants. Preferably, two or more surfactants may be used in terms of dispersion stabilization of the hydrophobic particles. More specifically, in consideration of the form of the hydrophobic particles, for example, the form of a metal salt of a saturated fatty acid, a nonionic surfactant and an anionic surfactant, for example, a nonionic surfactant bonded to a long-chain hydrocarbon having 10 or more carbon atoms and a sulfate-based anionic surfactant, may be used together to more effectively disperse the hydrophobic particles in water.

[0087] Examples of the cationic surfactant include dialkyldimethylammonium salts and alkylbenzylmethylammonium salts. Examples of the anionic surfactant include alkyl polyoxyethylene sulfates, monoalkyl sulfates, alkylbenzene sulfonates, monoalkyl phosphates, sulfates having functional groups containing long chain hydrocarbons or sodium salts thereof, such as sodium lauryl sulfate, sodium dodecyl sulfate, or sodium laureth sulfate. Examples of the amphoteric surfactant include alkyl sulfobetaines and alkyl carboxybetaines. Examples of the nonionic surfactant include polyoxyethylene alkyl ethers such as polyethylene glycol, polyoxyalkylene alkylphenyl ethers, polyoxyethylene arylphenyl ethers, fatty acid esters such as fatty acid sorbitan esters or glyceryl monostearate, alkyl monoglyceryl ethers, alkanolamides, and alkyl polyglucosides, but are not limited thereto.

[0088] The polymer used as the dispersion stabilizer may be polyalkylene glycol, polyethyleneimide, polyvinyl alcohol, polyacrylamide, polyvinylpyrrolidone, or the like.

[0089] Meanwhile, the first hydrophobic particles and the second hydrophobic particles can be used in an amount of 0.005 to 1 part by weight, respectively, relative to 100 parts by weight of the acrylic acid monomer. Specifically, for example, the first hydrophobic particles can be used in an amount of 0.005 parts by weight or more, or 0.007 parts by weight or more, but 0.25 parts by weight or less, 0.1 parts by weight or less, or 0.05 parts by weight or less, relative to 100 parts by weight of the acrylic acid monomer, and the second hydrophobic particles can be used in an amount of 0.025 parts by weight or more, or 0.035 parts by weight or more, but 0.75 parts by weight or less, 0.5 parts by weight or less, or 0.25 parts by weight or less, relative to 100 parts by weight of the acrylic acid monomer. In this case, the first hydrophobic particles and the second hydrophobic particles can be used in a weight ratio of 1:5 to 1:50, as described above.

[0090] In addition, the total weight of the first hydrophobic particles and the second hydrophobic particles may be 0.01 to 2 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the total content of the hydrophobic particles is too low, the hydrophobic particles may not function as a bubble stabilizer, and if the total content of the hydrophobic particle aqueous dispersion is too high, the surface tension of the superabsorbent resin may be reduced, and the flowability of the hydrophobic particles may be increased.

[0091] In addition, in the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the upper internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the upper internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.

[0092] In addition, the monomer composition may further include a polymerization initiator for initiating a polymerization reaction of the monomer. The polymerization initiator is not particularly limited as long as it is one that is generally used in the production of a highly water-absorbent resin.

[0093] Specifically, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation such as UV irradiation, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may be additionally included.

[0094] The photopolymerization initiator can be any compound capable of forming radicals by the action of light such as ultraviolet light, and is not limited in its composition.

[0095] The photopolymerization initiator may be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, a specific example of the acylphosphine may be commercially available lucirin TPO, i.e., phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. More various photoinitiators are well described in Reinhold Schwalm's book "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" p.115, and are not limited to the above examples.

[0096] The photopolymerization initiator may be contained in a concentration of about 0.01 to about 1.0% by weight based on the monomer composition. If the concentration of the photopolymerization initiator is too low, the polymerization rate may be slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.

[0097] The thermal polymerization initiator may be at least one selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of the persulfate initiator include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of the azo initiator include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. A wide variety of thermal polymerization initiators are well described in Odian's book 'Principle of Polymerization' (Wiley, 1981), p.203, and are not limited to the above examples.

[0098] The thermal polymerization initiator may be included in a concentration of about 0.001 to about 0.5 wt % based on the monomer composition. If the concentration of the thermal polymerization initiator is too low, additional thermal polymerization hardly occurs, and the effect of adding the thermal polymerization initiator may be small, whereas if the concentration of the thermal polymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.

[0099] The polymerization initiator can be used in an amount of 2 parts by weight or less per 100 parts by weight of the water-soluble ethylenically unsaturated monomer. That is, if the concentration of the polymerization initiator is too low, the polymerization rate may be slowed down, and a large amount of residual monomer may be extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network may be shortened, the content of water-soluble components may increase, and the water absorption capacity under pressure may decrease, which is not preferable, and the physical properties of the resin may be deteriorated.

[0100] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0101] The monomer composition including the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in such a solution state, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, may be appropriately adjusted in consideration of the polymerization time and reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80 wt%, or 15 to 60 wt%, or 30 to 50 wt%.

[0102] When the monomer composition has a solid content in the above range, it is possible to eliminate the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that occurs in the polymerization reaction of a high-concentration aqueous solution, and it may be advantageous to adjust the grinding efficiency when grinding the polymer described below.

[0103] The solvent that can be used in this case is not limited in composition as long as it can dissolve the above-mentioned components. For example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide can be used in combination.

[0104] (Stage 2) Next, the monomer composition is cross-linked and polymerized in the presence of a foaming agent or a bubble generator to produce a hydrogel polymer. In this step, bubbles are generated from the foaming agent or the bubble generator, and the two types of hydrophobic particles dispersed in water effectively capture the bubbles, thereby increasing the specific surface area of ​​the hydrogel polymer.

[0105] Meanwhile, the foaming agent may be a carbonate foaming agent, which foams during polymerization to form pores in the hydrogel polymer and increase the surface area, and may be at least one selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate.

[0106] The carbonate-based blowing agent can be used in an amount of 50 ppmw or more and 1 part by weight or less based on 100 parts by weight of the acrylic acid-based monomer. If the amount of the blowing agent is less than 50 ppmw, the role of the blowing agent may be insignificant, and if the amount of the blowing agent is more than 1 part by weight, the pores in the crosslinked polymer are too large, the gel strength of the produced superabsorbent resin is reduced, and the density is reduced, which may cause problems in distribution and storage. For example, the carbonate-based blowing agent may be more than 100 ppmw, but not more than 0.8 parts by weight, or not more than 0.7 parts by weight, based on 100 parts by weight of the acrylic acid-based monomer.

[0107] In addition, the carbonate-based foaming agent and the total content of the first hydrophobic particles and the second hydrophobic particles can be used in a weight ratio of 1:0.01 to 1:10. If the hydrophobic particle aqueous dispersion is used at an excessively low content compared to the carbonate-based foaming agent, it may be difficult to effectively capture the generated bubbles, resulting in a large pore size, and if the hydrophobic particle aqueous dispersion is used at an excessively high content compared to the foaming agent, it may be possible that the fluidity of the final product becomes high, the bulk density becomes low, and the surface tension becomes low. For example, the total weight of the first hydrophobic particles and the second hydrophobic particles may be 0.05 times or more, 0.1 times or more, or 0.5 times or more, but 5 times or less, 3 times or less, or 2 times or less, of the carbonate-based foaming agent.

[0108] Meanwhile, a bubble generator can be used instead of the foaming agent, and as such a bubble generator, a microbubble generator previously used for foaming a monomer composition in a process for producing a superabsorbent resin can be used without any particular limitation. One example of such a microbubble generator may be one in which the monomer composition is passed through a tubular flow path having a plurality of protruding pins installed therein at a predetermined supply speed, for example, 50 to 1500 (L / min), and the monomer composition is caused to collide with the protruding pins to foam. One example of such a microbubble generator is disclosed in Korean Patent Publication No. 2020-0128969, and it is of course possible to obtain and apply a commercial product applied in the examples described below.

[0109] Surfactants such as alkyl sulfate compounds and polyoxyethylene alkyl ether compounds, which are generally used as foam stabilizers, may not be used in steps 1 and 2. For example, alkyl sulfate compounds, which are anionic surfactants such as sodium dodecyl sulfate, ammonium lauryl sulfate, sodium lauryl ether sulfate, or sodium myreth sulfate, or alkyl ether sulfate compounds, which are nonionic surfactants such as polyoxyethylene lauryl ether, may not be used in steps 1 and 2. This can prevent the problem of low surface tension of the superabsorbent resin caused by the use of the surfactants.

[0110] On the other hand, the polymerization of the monomer composition in the presence of such an aqueous dispersion of hydrophobic particles is not particularly limited as long as it is a commonly used polymerization method.

[0111] Specifically, polymerization methods are broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Thermal polymerization can usually be carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization can be carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.

[0112] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft or by heating the reactor as described above may be several centimeters to several millimeters in size when discharged from the reactor outlet, depending on the type of the agitator shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer varies depending on the concentration of the monomer composition injected and the injection speed, and a hydrogel polymer having a weight average particle size of 2 to 50 mm is usually obtained.

[0113] In addition, when photopolymerization is performed in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a sheet-like hydrogel polymer having the width of the belt. In this case, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, but it is preferable to feed the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 10 cm is obtained. If the monomer composition is fed so that the thickness of the sheet-like polymer is too thin, the production efficiency is low, which is undesirable, and if the thickness of the sheet-like polymer exceeds 10 cm, the polymerization reaction may not occur uniformly over the entire thickness due to the excessive thickness.

[0114] (Stage 3) Then, the hydrogel polymer is dried and pulverized to form a powder-type base resin, and if necessary, a coarse pulverization step may be performed before the drying step to increase the efficiency of the drying step.

[0115] In this case, the crusher used is not limited in structure, and specifically may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.

[0116] The gel pulverization of the hydrogel polymer can be carried out so that the particle size of the hydrogel polymer is 0.01 mm to 50 mm, or 0.01 mm to 30 mm. That is, in order to increase the drying efficiency, it is preferable that the hydrogel polymer is pulverized into particles of 50 mm or less. However, since excessive pulverization may cause interparticle aggregation, it is preferable that the hydrogel polymer is gel pulverized into particles of 0.01 mm or more.

[0117] In addition, since the gel crushing of the hydrogel polymer is performed in a state where the water content is relatively low, the hydrogel polymer may stick to the surface of the gel crusher. To minimize this phenomenon, steam, water, surfactants, anti-aggregation agents (e.g., clay, silica, etc.), persulfate initiators, azo initiators, hydrogen peroxide, thermal polymerization initiators, epoxy crosslinkers, diol crosslinkers, crosslinkers containing acrylates with multifunctional groups of 2 or 3 or more functional groups, and monofunctional crosslinkers containing hydroxyl groups may be added to the hydrogel polymer as necessary.

[0118] After the gel crushing, the hydrogel polymer can be dried. The drying can be performed at a temperature of 120 to 250°C, preferably 140 to 200°C, and more preferably 150 to 200°C. The drying temperature can be defined as the temperature of the heat medium supplied for drying or the temperature inside the drying reactor containing the heat medium and the polymer in the drying process. If the drying temperature is low and the drying time is long, the process efficiency decreases, so in order to prevent this, the drying temperature is preferably 120°C or higher. In addition, if the drying temperature is higher than necessary, the surface of the hydrogel polymer may be excessively dried, which may increase the generation of fine powder in the subsequent crushing process and may deteriorate the physical properties of the final resin. In order to prevent this, the drying temperature is preferably 250°C or lower.

[0119] Meanwhile, the drying time can be about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0120] The drying method of the drying step can be selected and used without any limitation on the configuration as long as it is usually used as a drying process for a hydrogel polymer. Specifically, the drying step can be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after the drying step may be about 5 to about 10% by weight.

[0121] Then, the dried polymer obtained through the drying step is pulverized.

[0122] The base resin, which is a polymer powder obtained after the pulverization step, may have a particle size of about 150 to about 850 μm. Specific examples of the pulverizer used to pulverize to such a particle size include a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, and a jog mill, but the present invention is not limited to the above examples.

[0123] After the pulverization step, the base resin obtained after pulverization is classified according to particle size in order to control the physical properties of the superabsorbent resin powder to be the final product. Preferably, the polymer having a particle size of about 150 to about 850 μm is classified, and only the base resin having such a particle size may be subjected to the surface crosslinking reaction step.

[0124] (Stage 4) Meanwhile, after the base resin powder is produced through the above-mentioned classification process, the base resin powder can be surface-crosslinked by heat treatment in the presence of a surface crosslinking agent to form superabsorbent resin particles. The surface crosslinking is a process in which a crosslinking reaction is induced on the surface of the base resin powder in the presence of a surface crosslinking agent, and a surface modified layer (surface crosslinked layer) can be formed on the surface of the base resin powder through such surface crosslinking.

[0125] The content of the surface cross-linking agent can be appropriately selected depending on the type of the surface cross-linking agent to be added and the reaction conditions, and can be about 0.001 to about 5 parts by weight per 100 parts by weight of the base resin. If the content of the surface cross-linking agent is too low, the surface modification may not be performed properly, and the physical properties of the final resin may be deteriorated. On the other hand, if an excessive amount of the surface cross-linking agent is used, the basic water absorption performance of the resin may be deteriorated due to an excessive surface cross-linking reaction, which is not preferable.

[0126] There is no limitation on the constitution of the method for mixing the surface crosslinking agent with the base resin. A method of mixing the surface crosslinking agent and the base resin powder in a reaction tank, a method of spraying the surface crosslinking agent onto the base resin powder, a method of continuously supplying the base resin and the surface crosslinking agent to a continuously operated mixer, and the like can be used.

[0127] When the surface crosslinking agent is added, it may be added in the form of a surface crosslinking solution by mixing with water. When water is added, the surface crosslinking agent can be uniformly dispersed in the polymer. At this time, the content of the added water is preferably about 1 to about 10 parts by weight per 100 parts by weight of the base resin for the purpose of inducing uniform dispersion of the surface crosslinking agent and preventing the polymer powder from clumping, and at the same time optimizing the surface penetration depth of the surface crosslinking agent.

[0128] The surface cross-linking step may be carried out by using at least one selected from the group consisting of polyvalent metal salts, for example, aluminum salts, more specifically, sulfate, potassium salt, ammonium salt, sodium salt, and hydrochloride salt of aluminum, in addition to the surface cross-linking agent.

[0129] The polyvalent metal salt can be additionally used to further improve the liquid permeability of the superabsorbent resin prepared by the method of one embodiment. The polyvalent metal salt can be added to the surface crosslinking solution together with the surface crosslinking agent, and can be used in an amount of 0.01 to 4 parts by weight based on 100 parts by weight of the base resin powder.

[0130] Meanwhile, the surface crosslinking process can be carried out using a surface crosslinking liquid containing water and / or a hydrophilic organic solvent (e.g., an alcohol-based polar organic solvent such as methanol) as a liquid medium together with the above-mentioned surface crosslinking agent, etc. At this time, the content of water and the hydrophilic organic solvent can be adjusted and applied by controlling the addition ratio with respect to 100 parts by weight of the base resin powder in order to induce uniform dispersion of the surface crosslinking liquid, prevent the base resin powder from solidifying, and at the same time, optimize the surface penetration depth of the surface crosslinking agent.

[0131] There is no particular limitation on the configuration of the method for adding the above-mentioned surface cross-linking liquid to the base resin powder. For example, the surface cross-linking liquid and the base resin powder are mixed in a reaction tank, the surface cross-linking liquid is sprayed onto the base resin powder, or the base resin powder and the surface cross-linking liquid are continuously supplied to a continuously operated mixer and mixed therewith.

[0132] Specifically, the surface crosslinking can be performed by heating the base resin powder to which the surface crosslinking liquid has been added from an initial temperature of 20°C to 130°C over a period of 10 to 30 minutes to a maximum temperature of 140°C to 200°C, and maintaining the maximum temperature for 5 to 60 minutes. More specifically, the surface crosslinking can be performed by maintaining a maximum temperature of 140°C to 200°C or 170°C to 195°C for 5 to 60 minutes or 10 to 50 minutes.

[0133] By satisfying such surface cross-linking process conditions (particularly, the temperature rise conditions and the reaction conditions at the maximum reaction temperature), a highly water-absorbent resin that adequately satisfies the physical properties of one embodiment can be more effectively produced.

[0134] The temperature raising means for the surface cross-linking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. In this case, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but is not limited thereto, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat medium to be supplied. Meanwhile, examples of the heat source to be directly supplied include heating by electricity and heating by gas, but are not limited to the above examples. After forming a surface cross-linked layer on the surface of the base resin as described above, an inorganic substance can be additionally mixed.

[0135] The inorganic material may be, for example, one or more selected from the group consisting of silica, clay, alumina, a silica-alumina composite material, and titania, and preferably, silica.

[0136] The inorganic material can be used in an amount of 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.1 parts by weight or more, but not more than 5 parts by weight, or not more than 3 parts by weight, or not more than 1 part by weight, based on 100 parts by weight of the superabsorbent resin.

[0137] The superabsorbent resin obtained by the above-mentioned production method maintains excellent water absorption performance such as water retention capacity and pressure water absorption capacity, and has an improved water absorption speed, etc., and can satisfy all physical properties of one embodiment, and can be suitably used in sanitary materials such as diapers, especially ultra-thin sanitary materials with a reduced pulp content. EXAMPLES

[0138] <Production Example> The hydrophobic particle aqueous dispersions used in the following examples were prepared in the following manner.

[0139] Production Example 1: Production of calcium stearate aqueous dispersion (Ca-st) First, 50 g of water containing two or more surfactants (including polyoxyethylene alkyl ether-based nonionic surfactants and sulfate-based anionic surfactants) was added to a high shear mixer and heated to 165°C, and then 50 g of calcium stearate powder was added. Then, the mixture was stirred at 4000 rpm at normal pressure for 30 minutes to thoroughly pulverize the calcium stearate, thereby obtaining an aqueous dispersion in which 50% by weight of calcium stearate with an average particle size of 5 μm was dispersed. At this time, the pH of the aqueous dispersion was 9.5. The average particle size (D50) of the calcium stearate was measured / calculated as the particle size at the 50% point of the cumulative particle number distribution using a laser diffraction particle sizer (Microtrac S3500).

[0140] Production Example 2: Production of zinc stearate aqueous dispersion (Zn-st) First, 50 g of water containing two or more surfactants (including polyoxyethylene alkyl ether-based and fatty acid ester-based nonionic surfactants and sulfate-based anionic surfactants) was added to a high shear mixer and heated to 140°C, and then 50 g of zinc stearate powder was added. Next, the mixture was stirred at 4000 rpm at normal pressure for 30 minutes so that the zinc stearate was sufficiently pulverized, to obtain an aqueous dispersion Zn-st in which 50% by weight of zinc stearate having an average particle size of 0.1 μm was dispersed. At this time, the pH of the aqueous dispersion was 9.5, and the average particle size (D50) of the zinc stearate was measured / calculated in the same manner as in Preparation Example 1.

[0141] Production Example 3: Production of hydrophobic silica aqueous dispersion 100g of water was put into a high shear mixer, and while stirring at 5000 rpm, hydrophobic silica having an average particle size of 0.3 μm and a contact angle with water of 130° and hydrophobic silica having an average particle size of 3 μm and a contact angle with water of 130° were gradually added while being dispersed to 0.2 wt% and 2 wt% based on the total weight of the final aqueous dispersion. When the silica was completely added, it was stirred at 8000 rpm at a temperature of 45°C for 30 minutes. At this time, the pH of the aqueous dispersion was 9, and the average particle size (D50) of the hydrophobic silica was measured / calculated in the same manner as in Preparation Example 1.

[0142] Production Example 4: Production of hydrophobic silica aqueous dispersion A hydrophobic silica aqueous dispersion was prepared in the same manner as in Preparation Example 3, except that hydrophobic silica having an average particle size of 0.3 μm and a contact angle with water of 130° and hydrophobic silica having an average particle size of 3 μm and a contact angle with water of 130° were added in amounts of 0.2 wt % and 4 wt %, respectively, based on the total weight of the final aqueous dispersion.

[0143] Production Example 5: Production of hydrophobic silica aqueous dispersion A hydrophobic silica aqueous dispersion was prepared in the same manner as in Preparation Example 3, except that only hydrophobic silica having an average particle size of 0.3 μm and a contact angle with water of 130° was added in an amount of 0.2 wt % based on the total weight of the final aqueous dispersion.

[0144] <Example> Example 1 A monomer solution was prepared by mixing 100 parts by weight of acrylic acid with 0.27 parts by weight of ethylene glycol diglycidyl ether and 0.1 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide as a photoinitiator. Next, the monomer solution was continuously fed to a metering pump, and 160 parts by weight of 24% by weight aqueous sodium hydroxide solution was continuously fed at the same time. A monomer composition was prepared by high-speed line mixing with 6 parts by weight of 4% by weight aqueous sodium persulfate solution, 5 parts by weight of 4% by weight aqueous sodium bicarbonate solution, 0.2% by weight of hydrophobic silica having an average particle size of 0.3 μm prepared in Preparation Example 3, and 5 parts by weight of hydrophobic silica aqueous dispersion containing 2% by weight of hydrophobic silica having an average particle size of 3 μm. Through this transfer, the monomer composition was fed into a polymerization reactor consisting of a moving conveyor belt, and UV polymerization was performed for 3 minutes by irradiating ultraviolet rays through a UV irradiation device to prepare a hydrogel polymer in the form of a sheet.

[0145] The hydrogel polymer was cut into pieces with an average size of about 300 mm or less, and then fed into a crusher (equipped with a perforated plate containing a plurality of holes with a diameter of 10 mm) to cut the hydrogel. The crushed hydrogel was then dried in a dryer capable of shifting the airflow up and down. The hydrogel was uniformly dried by passing hot air at 180°C through the gel so that the moisture content of the dried powder was about 2% or less. The dried resin was crushed in a crusher and classified to obtain a base resin with a size of 150 to 850 μm.

[0146] Then, 6 parts by weight of a surface crosslinking agent aqueous solution containing 3 parts by weight of ethylene carbonate was sprayed onto 100 parts by weight of the prepared base resin powder, and the mixture was stirred at room temperature so that the surface crosslinking liquid was uniformly distributed on the base resin powder. Next, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction.

[0147] In the surface crosslinking reactor, the base resin powder was gradually heated from an initial temperature of about 80°C, and was operated so as to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was continued for an additional 15 minutes, and then a final superabsorbent resin sample was taken. After the surface crosslinking process, the superabsorbent resin of Example 1 having a particle size of 150μm to 850μm was produced by classifying the particles using a standard mesh sieve according to the ASTM standard.

[0148] Example 2 A superabsorbent resin was prepared in the same manner as in Example 1, except that instead of the carbonate-based foaming agent in Example 1, a bubble generator (OB-750S, O2 Bubbles) was used to generate bubbles of 10 to 300 μm for 5 minutes and the bubbles were injected into the neutralization liquid, and instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3, 5 parts by weight of the hydrophobic silica aqueous dispersion prepared in Preparation Example 4 containing 0.2 wt % of hydrophobic silica having an average particle size of 0.3 μm and 4 wt % of hydrophobic silica having an average particle size of 3 μm was used.

[0149] Example 3 A superabsorbent resin was prepared in the same manner as in Example 1, except that the hydrophobic silica aqueous dispersion prepared in Preparation Example 5 and the calcium stearate aqueous dispersion prepared in Preparation Example 1 were used instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3 in Example 1, in such a manner that 0.01 parts by weight of hydrophobic silica and 0.1 parts by weight of calcium stearate were added per 100 parts by weight of acrylic acid.

[0150] Example 4 A superabsorbent resin was prepared in the same manner as in Example 1, except that the zinc stearate aqueous dispersion prepared in Preparation Example 2 and the calcium stearate aqueous dispersion prepared in Preparation Example 1 were used instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3 in Example 1, in such a manner that the zinc stearate was added in an amount of 0.01 parts by weight per 100 parts by weight of acrylic acid, and the calcium stearate was added in an amount of 0.1 parts by weight per 100 parts by weight of acrylic acid.

[0151] Comparative Example 1 A superabsorbent resin was produced in the same manner as in Example 1, except that neither the carbonate-based foaming agent nor the hydrophobic particle aqueous dispersion was used, and the hydrogel was cut into pieces having an average size of about 300 mm or less, and then the pieces were put into a crusher (having a porous plate containing a plurality of holes having a diameter of 8 mm) and crushed under the respective conditions.

[0152] Comparative Example 2 A superabsorbent resin was prepared in the same manner as in Example 1, except that 1 part by weight of 3% by weight sodium dodecyl sulfate (SDS) solution was added instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3.

[0153] Comparative Example 3 A superabsorbent resin was prepared in the same manner as in Example 1, except that 7 parts by weight of 3 wt % hydrophilic silica aqueous dispersion (Klebosol 20, Merck) was added instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3.

[0154] Comparative Example 4 A superabsorbent resin was prepared in the same manner as in Example 1, except that 0.15 parts by weight of hydrophobic fumed silica powder (Reolosil® DM-30S, Tokuyama Co., Ltd.) was added instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3.

[0155] Comparative Example 5 A superabsorbent resin was prepared in the same manner as in Example 1, except that the hydrophobic silica aqueous dispersion prepared in Preparation Example 5, in which only hydrophobic silica having an average particle size of 0.3 μm was dispersed, was used instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3. At this time, the hydrophobic silica of Comparative Example 5 was added in an amount equal to the total weight of the two types of hydrophobic particles of Example 1.

[0156] Comparative Example 6 A superabsorbent resin was prepared in the same manner as in Example 1, except that only the calcium stearate aqueous dispersion prepared in Preparation Example 1 was used instead of the hydrophobic silica aqueous dispersion prepared in Preparation Example 3. At this time, the calcium stearate of Comparative Example 6 was added in an amount equal to the total weight of the two types of hydrophobic particles of Example 1.

[0157] Experimental Example 1: Measurement of pore size and particle count of superabsorbent resin In order to confirm the pore structure of the superabsorbent resin prepared in the examples and comparative examples, the surface and internal images of the superabsorbent resin particles were measured using a scanning electron microscope (SEM). Then, the number of pores whose longest diameter could be measured for each superabsorbent resin was calculated from the measured images, and the average diameter and maximum diameter of the pores were calculated based on the longest diameter of each pore for 300 or more pores. In addition, the average number of pores per particle was calculated from the number of pores whose longest diameter was measured. In addition, the pores whose longest diameter was greater than or less than the average diameter were classified into pores whose longest diameter was greater than or less than the average diameter, and the number of pores whose diameter was greater than the average diameter and the number of particles in which the pores were formed were measured, and the ratio of particles in which pores whose diameter was greater than the average diameter and less than the maximum diameter were calculated from this.

[0158] Among the measured SEM images, the images for Example 3 and Comparative Example 2 are shown in FIG. 1 and FIG. 2, respectively.

[0159] 1 and 2, it can be seen that the superabsorbent resin of Example 3 has a plurality of pores uniformly formed therein, with an average diameter of 1-100 μm and a maximum diameter of 280-300 μm, unlike the superabsorbent resin of Comparative Example 2. Additionally, it was confirmed that the superabsorbent resin of Example 3 has an average of 7 or more, for example, 7-30 pores formed per particle, and the ratio of particles having pores with diameters greater than the average diameter and less than the maximum diameter was about 20-40% by number of all superabsorbent resin particles.

[0160] In addition, although not shown in the present specification, it was confirmed that the highly water-absorbent resins of Comparative Examples 3 and 4 had no pores formed on the surface.

[0161] Experimental Example 2: Measurement of the physical properties of superabsorbent resin The superabsorbent resins prepared in the above examples and comparative examples were evaluated for physical properties by the following methods, and the results are shown in Table 1 below. Unless otherwise indicated, all the processes for evaluating the physical properties below were carried out in a constant temperature and humidity room (23±0.5°C, relative humidity 45±0.5%), and the average value of three measurements was used to prevent measurement errors. In addition, in the evaluation of the physical properties below, saline or salt water refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution.

[0162] (1)Centrifuge Retention Capacity (CRC) The centrifugal retention capacity (CRC) was measured based on the water absorption capacity under no load according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 241.3. The superabsorbent resin W0 (g, approximately 0.2 g) was evenly placed in a nonwoven envelope, sealed, and then immersed in a physiological saline solution of 0.9 wt% sodium chloride solution at room temperature. After 30 minutes, the envelope was centrifuged at 250 G for 3 minutes to remove water, and the mass of the envelope W2 (g) was measured. In addition, the same operation was performed without using the superabsorbent resin, and the mass W1 (g) at that time was measured. The CRC (g / g) was calculated using the masses obtained in this way according to the following formula 1 to confirm the water retention capacity.

[0163] [Formula 1] CRC(g / g)={[W2(g)-W1(g)-W0(g)] / W0(g)}

[0164] (2) Absorbtion Under Pressure (AUP) The absorbency under pressure (AUP) of the superabsorbent resins of the Examples and Comparative Examples was measured according to the method of the European Disposables and Nonwovens Association standard EDANA WSP 242.3.

[0165] First, a stainless steel 400 mesh iron net was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. Resins W0 (g, 0.90 g) obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were evenly spread on the iron net under conditions of a temperature of 23±2°C and a relative humidity of 45%, and a piston capable of evenly applying a load of 4.83 kPa (0.7 psi) thereon had an outer diameter slightly smaller than 60 mm and had no gap with the inner wall of the cylinder so that the up and down movement was not hindered. At this time, the weight W3 (g) of the device was measured.

[0166] A glass filter with a diameter of 125 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and physiological saline composed of 0.90 wt% sodium chloride was placed so that it was at the same level as the upper surface of the glass filter. The measuring device was placed on the glass filter, and the liquid was absorbed under load for 1 hour. After 1 hour, the measuring device was lifted up and its weight W4 (g) was measured.

[0167] Using the masses thus obtained, AUP (g / g) was calculated according to the following formula 2 to confirm the water absorption capacity under pressure.

[0168] [Formula 2] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0169] In the above formula 2, W0 (g) is the initial weight of the superabsorbent polymer (g), W3(g) is the total weight of the superabsorbent polymer and the weight of an apparatus capable of applying a load to the superabsorbent polymer; W4(g) is the total weight of the superabsorbent polymer and the weight of a device capable of applying a load to the superabsorbent polymer after the superabsorbent polymer is allowed to absorb saline solution under a load (0.7 psi) for 1 hour.

[0170] (3) Water absorption rate (Vortex time) The water absorption rate (vortex time) of the superabsorbent resins of the above examples and comparative examples was measured by the following method.

[0171] (i) First, 50 mL of 0.9% salt water was poured into a 100 mL beaker with a flat bottom using a 100 mL measuring cylinder. (ii) The beaker was then placed in the center of a magnetic stirrer and a circular magnetic bar (diameter 30 mm) was placed in the beaker. (iii) The stirrer was then operated so that the magnetic bar was stirring at 600 rpm, and the lowest point of the vortex generated by the stirring was brought into contact with the top of the magnetic bar. (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, 2±0.01 g of the superabsorbent resin sample was added while simultaneously starting a stopwatch, and the time until the liquid surface became completely horizontal while the vortex disappeared was measured in seconds, and this was regarded as the water absorption speed.

[0172] (4) Surface tension (S / T) The surface tension of the superabsorbent resins of the above Examples and Comparative Examples was measured as follows.

[0173] (i) First, 40 g of physiological saline solution composed of 0.9 wt % sodium chloride was placed in a 50 mL beaker, and then a circular magnetic bar (diameter 30 mm) was placed therein and stirred at 350 rpm for 3 minutes. (ii) Next, 0.5 g of superabsorbent resin was added to the stirred solution and stirred for an additional 3 minutes, after which the stirring was stopped and the solution was left to stand for 2 minutes to allow the swollen superabsorbent resin to sink to the bottom. (iii) The supernatant liquid (the solution just below the surface) was then extracted with a pipette and transferred to another clean cup, after which the surface tension was measured using a surface tension meter (Force Tensiometer-K11 / K100, manufactured by Kruss).

[0174] [Table 1]

[0175] As shown in Table 1, the superabsorbent resin of the Example, which was prepared by polymerization of monomers in the presence of an aqueous dispersion containing two types of hydrophobic particles, was found to have a pore structure in which a large number of pores, an average of 7 or more per particle, had an average diameter of 100 μm or less and a maximum diameter of 300 μm or less, unlike the superabsorbent resin of the Comparative Example. In addition, it was found that the ratio of particles in which pores having a diameter greater than the average diameter were formed was about 10-50%, and that fine pores close to the average diameter were formed very uniformly on the remaining majority of particles.

[0176] Also, it can be confirmed that the superabsorbent resins of the Examples exhibit a certain level of surface tension and a high water absorption rate without any decrease in water absorption performance compared to the superabsorbent resins of the Comparative Examples.

[0177] Specifically, the superabsorbent resin of the embodiment shows a significantly improved water absorption rate compared to Comparative Example 1, which does not use a foaming agent or a bubble stabilizer. Also, the superabsorbent resin of the embodiment shows a high surface tension while having a high water absorption rate compared to Comparative Example 2, which uses sodium dodecyl sulfate (SDS), which is mainly used as a conventional bubble stabilizer.

[0178] In addition, it was confirmed that the superabsorbent resins of the above Examples have a developed porous structure in which a large number of uniform-diameter micropores are formed, and thus exhibit a fast water absorption rate, compared to the superabsorbent resin of Comparative Example 5, which uses only a hydrophobic silica aqueous dispersion having an average particle size of less than 1 μm, and the superabsorbent resin of Comparative Example 6, which uses only a hydrophobic silica aqueous dispersion having an average particle size of more than 1 μm.

[0179] In particular, in the case of the superabsorbent resin of Comparative Example 3, which used a hydrophilic silica aqueous dispersion, and the superabsorbent resin of Comparative Example 4, which used hydrophobic silica in powder form, it was confirmed that a pore structure could not be formed on the surface, making it impossible to improve the water absorption rate.

Claims

1. A base resin in powder form containing a crosslinked polymer of an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and an internal crosslinking agent; and A superabsorbent resin comprising a surface cross-linked layer formed on the base resin and in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent, The superabsorbent resin has an average of 7 or more pores per particle, the pores have an average diameter of 100 μm or less and a maximum diameter of 300 μm or less, and particles having pores having a diameter between the average diameter and the maximum diameter account for 10 to 50% by number of all superabsorbent resin particles, The highly absorbent resin has a surface tension of 65 mN / m or more and a water absorption rate (vortex time) of 40 seconds or less at 24.0°C; the superabsorbent resin includes first hydrophobic particles and second hydrophobic particles; the first hydrophobic particles have an average particle size of less than 1 μm; the second hydrophobic particles have an average particle size of 1 μm or more; a ratio of an average particle size of the second hydrophobic particles to an average particle size of the first hydrophobic particles is 5 to 100; The superabsorbent resin, wherein the first hydrophobic particles and the second hydrophobic particles are contained in a weight ratio of 1:5 to 1:

50.

2. The superabsorbent resin according to claim 1, wherein the first hydrophobic particles and the second hydrophobic particles are each independently selected from the group consisting of hydrophobic silica, metal salts of fatty acids having 7 to 24 carbon atoms, and hydrophobic organic particles.

3. 3. The highly water-absorbent resin according to claim 2, wherein the metal salt of a fatty acid is one or more metal salts of stearic acid selected from the group consisting of calcium stearate, magnesium stearate, sodium stearate, zinc stearate, and potassium stearate.

4. 2. The superabsorbent polymer of claim 1, wherein the superabsorbent polymer contains an average of 7 to 30 pores per particle.

5. The highly water-absorbent resin according to claim 1, wherein the surface cross-linking agent comprises at least one selected from the group consisting of polyhydric alcohol compounds, polyhydric epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, and alkylene carbonate compounds.

6. The superabsorbent polymer according to any one of claims 1 to 5, wherein the superabsorbent polymer has a centrifugation retention capacity (CRC) of more than 27 g / g as measured by EDANA method WSP241.3 and an absorbency under pressure (AUP) of more than 20 g / g at 0.7 psi as measured by EDANA method WSP242.

3.

7. A step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, a polymerization initiator, an internal crosslinking agent, and an aqueous dispersion of hydrophobic particles (step 1); Step 2: cross-linking and polymerizing the monomer composition in the presence of a foaming agent or bubble generator to produce a hydrogel polymer; drying and grinding the hydrogel polymer to form a base resin in powder form (Step 3); and and (4) further cross-linking the surface of the base resin in the presence of a surface cross-linking agent to form a surface cross-linked layer. the hydrophobic particle aqueous dispersion is a colloidal solution in which first hydrophobic particles and second hydrophobic particles are dispersed, and a ratio of an average particle size of the second hydrophobic particles to an average particle size of the first hydrophobic particles is 5 to 100, the first hydrophobic particles have an average particle size of less than 1 μm; the second hydrophobic particles have an average particle size of 1 μm or more; The first hydrophobic particles and the second hydrophobic particles are contained in a weight ratio of 1:5 to 1:

50.

8. The method for producing a highly water-absorbent resin according to claim 7, wherein the first hydrophobic particles and the second hydrophobic particles are each used in an amount of 50 ppmw to 1 part by weight based on 100 parts by weight of the acrylic acid monomer.

9. The method for producing a highly water-absorbent resin according to claim 7, wherein the total weight of the first hydrophobic particles and the second hydrophobic particles is 0.01 to 2 parts by weight based on 100 parts by weight of the acrylic acid monomer.

10. The method for producing a superabsorbent resin according to claim 7, wherein the first hydrophobic particles and the second hydrophobic particles are dispersed in the hydrophobic particle aqueous dispersion in the presence of at least a nonionic surfactant and an anionic surfactant.

11. The method for producing a superabsorbent resin according to claim 7, wherein the surface crosslinking agent comprises at least one selected from the group consisting of polyhydric alcohol compounds, polyfunctional epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, and alkylene carbonate compounds.

12. The method for producing a highly water-absorbent resin according to claim 7, wherein the surface crosslinking is carried out by heating the mixture from an initial temperature of 20°C to 130°C over a period of 10 to 30 minutes to a maximum temperature of 140°C to 200°C, and maintaining the maximum temperature for 5 to 60 minutes.

Citation Information

Patent Citations

  • Particulate water absorbent

    JP2004261796A

  • Method for producing porous superabsorbent resin

    JP2019518815A

  • Highly water-absorbent resin and method for producing the same

    JP2019518839A

  • Method for producing porous superabsorbent resin and porous superabsorbent resin

    JP2019519663A